Pertanggungjawaban Pidana Terhadap Pelaku Penyebar Berita Bohong yang Menyebabkan Kerugian Konsumen (Dengan Menggunakan Aplikasi Termux) - Toby Tiovan; Gloria Melisa Febriana Simatupang; Immanuel Simanjuntak (Verdict: Journal of Law Science, 2026)
The development of information and communication technology has significantly transformed electronic transactions while also increasing the risk of cybercrime, including the dissemination of false or misleading information that causes consumer losses. This issue becomes more complex when technology-based applications such as Termux, which are legally intended for system administration and programming purposes, are misused to facilitate cybercrime. This study aims to analyze the criminal liability of perpetrators who disseminate false information using the Termux application and to examine the judges’ legal considerations in Decision Number 1295/Pid.Sus/2023/PN Medan. This research employs a normative legal method using statutory, case, and conceptual approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively. The findings reveal that perpetrators may be held criminally liable under Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the Electronic Information and Transactions Law, provided that the elements of intent, unlawful conduct, and consumer losses are established. The court’s decision was based not only on juridical considerations but also on sociological and philosophical aspects to ensure justice, legal certainty, and legal utility. Furthermore, consumers who suffer losses are legally protected under both the Electronic Information and Transactions Law and the Consumer Protection Law through criminal and civil remedies. This study contributes to the development of criminal and cyber law by strengthening legal analysis of criminal liability and consumer protection in Indonesia’s digital environment.